2018
DOI: 10.1161/circulationaha.117.031560
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of High-Sensitivity Troponin T in Chronic Heart Failure

Abstract: In chronic heart failure, high-sensitivity troponin T is a strong and independent predictor of all-cause and cardiovascular mortality, and of hospitalization for cardiovascular causes, as well. This biomarker then represents an additional tool for prognostic stratification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
146
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 177 publications
(166 citation statements)
references
References 42 publications
8
146
0
6
Order By: Relevance
“…The design and main results of our IPD meta-analysis on hs-TnT in CHF have been reported in detail. [6] Briefly, in April 2017, two authors (AA and GV) independently searched 4 databases (Medline, EMBASE, Cochrane Library, and Scopus), using the following search terms: "troponin" AND "heart failure" OR "cardiac failure" OR "cardiac dysfunction" OR "cardiac insufficiency" OR "left ventricular dysfunction". The inclusion criteria were: English language; patients aged ≥18 years and diagnosed with HF; reported enrolment of outpatients or patients undergoing elective admission; reported use of a hs-TnT and/or I assay; information on patient prognosis; authors' availability to provide IPD data.…”
Section: Search Study Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The design and main results of our IPD meta-analysis on hs-TnT in CHF have been reported in detail. [6] Briefly, in April 2017, two authors (AA and GV) independently searched 4 databases (Medline, EMBASE, Cochrane Library, and Scopus), using the following search terms: "troponin" AND "heart failure" OR "cardiac failure" OR "cardiac dysfunction" OR "cardiac insufficiency" OR "left ventricular dysfunction". The inclusion criteria were: English language; patients aged ≥18 years and diagnosed with HF; reported enrolment of outpatients or patients undergoing elective admission; reported use of a hs-TnT and/or I assay; information on patient prognosis; authors' availability to provide IPD data.…”
Section: Search Study Study Selectionmentioning
confidence: 99%
“…[5] In a recent meta-analysis concerning 9289 individual patient data (IPD) from 11 cohorts, we confirmed a strong prognostic value of high-sensitivity (hs) TnT assay for all-cause death, cardiovascular death, and cardiovascular hospitalization, additive to established risk markers (sex, age, ischemic vs. nonischemic etiology, left ventricular ejection fraction -LVEF, estimated glomerular filtration rate -eGFR, and also NT-proBNP). [6] The mechanisms leading to the production and release of natriuretic peptides in HF include hemodynamic overload and neurohormonal activation, while troponin elevation is driven by ongoing cardiomyocyte necrosis/apoptosis. [7] Other biomarkers could contribute to refine risk stratification: in particular, a subclinical myocardial inflammation is frequently observed in HF and hs-C-reactive protein (hs-CRP) carries prognostic significance in chronic HF.…”
Section: Introductionmentioning
confidence: 99%
“…Although the value of high sensitivity TnT (hs‐TnT) may be greater than p99 (14 ng/L), elevations less than x 2 do not correlate with a higher mortality at one year 14 . A meta‐analysis of chronic HF set the optimum cut‐off for hs‐TnT for all‐cause mortality at 18 ng/L 15 . The interpretation and clinical utility of elevated Tn levels in patients with AHF is controversial, and it would be of interest to establish an optimal cut‐off above which mortality clearly rises.…”
Section: Introductionmentioning
confidence: 99%
“…Troponin is not routinely determined in clinical practice, even if in HF its release is promoted by several mechanisms, namely myocardial ischaemia attributable to coronary artery disease or microcirculatory dysfunction, damage elicited by neurohormonal overactivation, inflammatory or infiltrative processes, myocardial apoptosis or autophagy, and increased protein turnover . A recent meta‐analysis of Aimo et al . concluded that in chronic HF, high‐sensitivity troponin T (hs‐TnT) is independently associated with all‐cause mortality, cardiovascular mortality and cardiovascular hospitalization.…”
mentioning
confidence: 99%